Oxidative status of erythrocytes, hyperglycemia, and hyperlipidemia in diabetic cats - Eric Zini; Gianfranco Gabai; Elena Salesov; Gabriele Gerardi; Laura Da Dalt; Thomas A. Lutz; Claudia E. Reusch (Journal of Veterinary Internal Medicine, 2020)
Abstract Background Erythrocytes of diabetic cats have decreased superoxide dismutase activity, possibly indicative of oxidative stress. Hypothesis Erythrocytes of diabetic cats undergo oxidative stress, which is caused by hyperglycemia and hyperlipidemia, and improves with treatment. Animals Twenty‐seven client‐owned cats with diabetes mellitus, 11 matched healthy cats, and 21 purpose‐bred healthy cats. Methods Prospective study. Advanced oxidized protein products, carbonyls (protein oxidation by‐products), and thiols (antioxidants) were quantified in erythrocyte membrane, thiobarbituric acid reactive substances (TBAR, lipid peroxidation by‐products), and thiols in erythrocyte cytoplasm of all cats. Comparison were performed between diabetic and matched healthy cats, between diabetic cats achieving remission or not, and among purpose‐bred cats after 10 days of hyperglycemia (n = 5) or hyperlipidemia (n = 6) versus controls treated with saline (n = 5) or untreated (n = 5). Results Compared with controls, erythrocytes of diabetic cats initially had higher median membrane carbonyls (4.6 nmol/mg total protein [range: 0.1‐37.7] versus 0.7 [0.1‐4.7], P < .001) and lower cytoplasmic TBAR (1.9 nmol/mg [0.5‐2.4] versus 2.4 [1.4‐3.5] P < .001), and thiols (419 nmol/mg [165‐621] versus 633 [353‐824], P < 0.001). After 12‐16 weeks of treatment in diabetic cats, carbonyls decreased by 13% (P < .001), but remained higher (P < .001) and TBAR and thiols lower (P = .02, P < .001) than those in controls. No differences were observed between diabetic cats achieving remission or not, and among purpose‐bred cats. Conclusions and Clinical Importance Diabetes mellitus is associated with increased protein oxidation and reduced antioxidant defenses, which persist during treatment and remission, although mild improvement in protein oxidation occurs. Short‐term hyperglycemia or hyperlipidemia does not cause oxidative stress. The reason for decreased TBAR remains unknown.